Evaluation of immunomodulatory drugs in multiple myeloma: single center experience - Ozkan, Melda Comert (Am J Blood Res, 2015)
Objective: Multiple myeloma (MM) comprises 1% of all cancers and 10% of hematologic malignancies and known as an incurable disease. The introduction of immunomodulatory drugs (IMiDs) has brought a major shift in therapeutic paradigm in the treatment of newly diagnosed and relapsed/refractory MM patients. The aim of this study was to evaluate the relationship between response status and hematological parameters in patients with MM treated with thalidomide or lenalidomide. Methods: Sixty-eight patients who were treated with IMiDs in Ege University, School of Medicine, Department of Hematology, between 2005 and 2012, were evaluated, retrospectively. Results and Conclusion: We could not find any difference between the hematological parameters before and after the treatment neither with thalidomide nor lenalidomide. However, the heterogenity of our groups, the difference in treatment strategies and potential side effects would have an impact on this result. It is needed to perform prospective clinical trials to prove that whether correction of hematological parameters would reflect the response status in patients with myeloma that treated with IMiDs.